Product Recalls in the Medical Device Industry: An Empirical Exploration of the Sources and Financial Consequences - Thirumalai, Sriram; Sinha, Kingshuk K. (Management Science, 2011)
Medical devices play an increasingly significant role in the delivery of health care today. However, persistent quality problems with medical devices and the associated recalls present potential health risks to patients and personnel using these devices. This study addresses three key issues in this regard. First, it empirically assesses the financial implications of medical device recalls to understand if these consequences are severe enough to deter firms from introducing potentially hazardous medical devices into the market, as can be inferred from the literature. Second, the study considers a cross section of medical device manufacturers to examine the effect of firm characteristics on the costs of poor quality. Third, in an attempt to explore the sources of recalls, this study investigates firm characteristics that are likely to be associated with device recalls. The econometric analyses in the study are based on data from manufacturers in the medical device industry over a four-year period (2002–2005). Contrary to our expectations, the findings of the study indicate that at an aggregate level, the market penalties for medical device recalls are not significant, i.e., at the aggregate level, the costs of poor quality are not severe. Furthermore, we find that the magnitude of financial consequences of device recalls is affected by the product scope, sales, growth prospects, and the capital structure of a firm. In our analyses exploring the sources of device recalls, we find that firms with a research and development focus, developing broader product portfolios, have a higher likelihood of device recalls. Also, we find that the likelihood of recalls decreases with prior recall experience, indicating the presence of learning. Implications of the study findings, limitations, and directions for future research are identified. This paper was accepted by Sampath Rajagopalan, operations and supply chain management.